U.S.‐Thai Consortium for the development of pharmacy education in Thailand: History, progress, and impact. Issue 5 (9th June 2020) - Nathisuwan, Surakit; Pattharachayakul, Sutthiporn; Subongkot, Suphat; Doungngern, Thitima; Jones, Sirada M.; Engle, Janet P.; Lau, Alan; Katz, Michael D.; Moreton, Julian Edward; Ryan, Melody
Abstract: In Thailand during the early 1990s, there was a need for an increased number of pharmacists and expansion of their knowledge and skills to address the need of the nation. Leaders of the Thai pharmacy education community at the time crafted a long‐term plan aiming to expand the pharmacy educator workforce at a national scale through the financial support of the Royal Thai Government. This led to the establishment of the United States‐Thai Consortium for the Development of Pharmacy Education in Thailand in 1994. The aim of the Consortium was to advance pharmacy education in Thailand through the support of leading U.S. pharmacy schools using both short‐term and long‐term trainings. Twenty plus years later, pharmacy education and practice in Thailand have changed dramatically. The number of faculties (schools) of pharmacy in Thailand has increased from 10 in 1993 to 19 in 2013. The ratio of pharmacists to population has decreased from 1:10532 in 1994 to 1:2261 in 2016. The professional pharmacy curriculum has changed from a 5‐year bachelor to a 6‐year Doctor of Pharmacy (Pharm.D.) degree. The role of Thai pharmacists has been endorsed by national health service initiatives and practice guidelines. Currently, 7 universities offer residency/fellowship programs. The 8 Thai founding institutions of the Consortium are now publishing over 500 papers in high‐quality international journals annually. In summary, pharmacy education, practice, and research in Thailand have improved dramatically through the U.S.‐Thai Pharmacy Consortium. This bi‐national model of knowledge and skill transfer may serve as an example for how a large‐scale international partnership can facilitate a rapid and positive transformation of pharmacy in a developing country. Local adjustment and adaptation are required to reflect national identity and to suit the local context.